1996
DOI: 10.1128/jcm.34.5.1161-1165.1996
|View full text |Cite
|
Sign up to set email alerts
|

Role of stool screening tests in diagnosis of inflammatory bacterial enteritis and in selection of specimens likely to yield invasive enteric pathogens

Abstract: The Leuko-Test yielded a negative predictive value of 98.4% when it was used to screen 325 patients for inflammatory bacterial enteritis and a negative predictive value of 99.4% when it was used to screen 416 stool specimens for those from which enteric pathogens would likely be recovered when cultured. Neither microscopy for fecal leukocytes nor an assay for fecal occult blood, alone or in combination, allowed for the reliable detection of invasive bacterial enteritis or the reliable selection of specimens fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…FLF is a reliable marker of intestinal inflammation, since titers of Ͼ1:50 are not seen in healthy controls but are almost always present in highly inflammatory diseases like shigellosis. Recent studies have shown that FLF titers detect bacterial colitis with greater sensitivity than microscopic examination for fecal WBCs (18,25,26,29) and even stool culture (28). In fact, in a multivariate regression model, an elevated FLF titer predicts a positive C. difficile toxin assay in the setting of nosocomial diarrhea better than any other clinical or laboratory parameter (18).…”
Section: Discussionmentioning
confidence: 99%
“…FLF is a reliable marker of intestinal inflammation, since titers of Ͼ1:50 are not seen in healthy controls but are almost always present in highly inflammatory diseases like shigellosis. Recent studies have shown that FLF titers detect bacterial colitis with greater sensitivity than microscopic examination for fecal WBCs (18,25,26,29) and even stool culture (28). In fact, in a multivariate regression model, an elevated FLF titer predicts a positive C. difficile toxin assay in the setting of nosocomial diarrhea better than any other clinical or laboratory parameter (18).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Intestinal inflammation has been reported in cases of CDAD, and the lactoferrin test and oc-cult blood tests have been used for the diagnosis of inflammatory diarrhea including C. difficile infection. 3,[22][23][24] In this study, we determined the prevalence of C. difficile in the Vhembe district population and the profile of toxigenicity of the strains present in the stools by detecting the tcdA (toxin A), tcdB (toxin B), and cdtA and cdtB (binary toxin: CDT) genes using specific PCR protocols in association with diarrhea, lactoferrin, and occult blood. The putative negative regulator for toxins A and B (tcdC) was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…The value of indiscriminate bacteriologic culture of feces in human patients has been examined and found to be generally low. [1][2][3] Although similar studies have not been performed in canine patients, some authors warn against routine bacteriologic culture of feces because of suspicion of the same relative yield. 4,5 The organisms most commonly considered to be causes of bacterial-associated diarrhea in dogs are Salmonella spp, Campylobacter spp, Clostridium perfringens, and C difficile.…”
mentioning
confidence: 99%